The Impact of Zinc Supplementation on Critically Ill Patients With Acute Kidney Injury: A Propensity Score Matching Analysis - Xia, Wenkai; Li, Chenyu; Zhao, Danyang; Xu, Lingyu; Kuang, Meisi; Yao, Xiajuan; Hu, Hong (Frontiers in Nutrition, 2022)
Background: Zinc is an essential trace element that is involved in multiple metabolic processes. The effects of zinc use on outcomes in critically ill patients with acute kidney injury (AKI) remains unknown. The present study aimed to investigate the effectiveness of zinc supplementation in critically ill patients with AKI. Methods: Critical ill patients with AKI were identified from the Medical Informative Mart for Intensive Care (MIMIC)-III database. Prosperity score matching (PSM) was applied to match patients receiving zinc treatment to those without zinc treatment. The association between zinc sulfate use and in-hospital mortality and 30-day mortality, need for renal replacement therapy (RRT) and length of stay was determined by the logistic regression model and Cox proportional hazards model. Results: A total of 9811 AKI patients were included in the study. After PSM, 222 pairs of patients were matched between the patients who received zin treatment and those without treatment. Zinc supplementation was associated with reduced in-hospital mortality (HR 0.48, 95%CI 0.28-0.83, P=0.009) and 30-day mortality (HR0.51, 95%CI 0.30-0.86, P=0.012). In the subgroup analysis, zinc use was associated with reduced in-hospital mortality in patients with AKI stage 1 and those with sepsis. Conclusions: Zinc supplementation was associated with improved survival in critically ill patients with AKI, it was especially effective in those with AKI stage1 and sepsis. However, the results need to be verified in randomized controlled trials.